The branch - Messier, Mireille 1971- (Kids Can Press, 2016)
"When a branch from her beloved tree snaps off in an icy storm, a plucky girl refuses to let it be hauled away. Her neighbor, Mr. Frank, says it's full of potential. So with imagination and spirit (and Mr. Frank's help), the girl creates something whole and new out of the broken branch, to be enjoyed again and again!"--Cover flap
"Edited by Yasemin Uçar"--Copyright page
Keywords: Trees / Juvenile fiction; Storms / Juvenile fiction; Girls / Juvenile fiction; Trees / Fiction; Storms / Fiction; Woodworking / Fiction; Girls / Fiction; JUVENILE FICTION / Family / Multigenerational; JUVENILE FICTION / Imagination & Play; JUVENILE FICTION / Nature & the Natural World / Weather; Girls; Storms; Trees; Picture books; Fiction; Juvenile works; Picture books for children; Bilderbuch